The significance of Enterprise Architecture in driving Digital Transformation on Public sectors - Modikwa MAKOVHOLOLO; Phathutshedzo MAKOVHOLOLO; Tefo SEKGWELEO (International Journal of Applied Methods in Electronics and Computers, 2021)
Industries and organizations have recently engaged in initiatives focusing on the exploration of methods and models for digital transformation. As a result, it somehow remains unclear to many business leaders as to what digital transformation mean. However, based on the mere fact that industries at large are embracing the concept of digital transformation and initiating programs around this concept. It can only mean that there are common benefits envisioned though, the main challenge to be addressed is how best can organizations get over the initial humps from vision to execution. Enterprise Architecture (EA) discipline on the other hand, have been praised for being a good approach on mapping the future state of the enterprise ranging from business processes re-organization to technology alignment. Hence, the focus of this paper is to examine the capability of EA approach in driving the digital transformation, more so in the public sector. This study employed a case study research approach to investigate the significance of EA in driving digital transformation on public sectors. Semi-Structured technique was used as a method for collecting data. The analysis was carried out, using Actor Network Theory (ANT). Through the findings that was established using ANT as a framework for driving a digital transformation for public sectors was proposed.